KEABSAHAN KONTRAK DALAM TRANSAKSI KOMERSIAL ELEKTRONIK - Totok Tumangkar (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
The development of technology, especially the Internet, providing a lot of convenience to human life. However, on the other hand, this progress also brings new problems. E-commerce as a form of trade that is currently undergoing rapid development can not be separated from the problems in the implementation. From the legal aspect of the issue will arise as to the validity of an electronic contract and issues regarding whether or not an electronic contract serve as evidence in the trial. In this paper aims to see whether an electronic contract can be said to be valid and how the power of electronic contracts in the event of a dispute, especially in Indonesia. This indicates that there are differences of opinion about the validity of electronic contracts and electronic contracts as evidence the judge (not valid and can not be used as evidence), the perpetrators of e-commerce (electronic contracts are valid and can be used as evidence), and notaries (notary found one electronic contract is valid and can be used as evidence, two other notaries people found the contract is done electronically could be said legitimately but still difficult to be accepted as evidence). From this paper it can be concluded that there is still uncertainty regarding the validity and strength of the contract is done electronically as evidence.